2020
DOI: 10.4103/jhrs.jhrs_142_18
|View full text |Cite
|
Sign up to set email alerts
|

CYP19A1 gene expression in patients with polycystic ovarian syndrome

Abstract: Context: Polycystic ovarian syndrome (PCOS) is a common endocrine system disorder among the women of reproductive age, yet the etiology of PCOS remains unclear. Infertility in females with PCOS can be caused by anovulation, high luteinizing hormone levels, and hyperandrogenism. Aims: This research analyzed the role of the aromatase gene (CYP19A1) in PCOS pathogenesis. Settings and Design: This study used an observational, cross-sectional desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…A prospective crosssectional study showed that IR secondary to PCOS insulinmediated decreased glucose uptake and increased insulin secretion was partly due to decreased GLUT4 expression in adipocytes without a compensatory increase in GLUT1 expression (34). The analysis of signaling components of the IRS/PI3K/AKT pathway showed that the expression of GLUT4 was significantly decreased in PCOS patients and the IR control group (35). Their results point to a new mechanism by which miR-93 regulates insulin-stimulated glucose uptake and demonstrates that the upregulated expression of miR-93 in all women with IR with or without PCOS may be the cause of IR in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective crosssectional study showed that IR secondary to PCOS insulinmediated decreased glucose uptake and increased insulin secretion was partly due to decreased GLUT4 expression in adipocytes without a compensatory increase in GLUT1 expression (34). The analysis of signaling components of the IRS/PI3K/AKT pathway showed that the expression of GLUT4 was significantly decreased in PCOS patients and the IR control group (35). Their results point to a new mechanism by which miR-93 regulates insulin-stimulated glucose uptake and demonstrates that the upregulated expression of miR-93 in all women with IR with or without PCOS may be the cause of IR in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the influence of the inflammatory response on the production of androgens as a result of posttranscriptional regulation of gene expression in PCOS are being constantly updated [ 209 , 213 , 214 ]. Thus, any epigenetic regulation that leads to a decrease in the expression of the CYP19A1 (aromatase) gene in granulosa cells or a decrease in the relative expression rate of GC aromatase, as well as producing upregulation of AR and increased activity of the key enzymes essential for androgen biosynthesis in thecal cells (i.e., CYP11A1, CYP17, and HSD3B2), should be considered in the context of inflammation in PCOS [ 211 , 215 , 216 , 217 ] ( Figure 3 ).…”
Section: Epigenetic Modulation Of Androgenic Activity In Response To ...mentioning
confidence: 99%
“…In granulosa cells, SF-1 can bind to the cAMP response element and act on aromatase promoter II, thereby causing estrogen production ( 101 ). Abnormally expressed SF-1 in endometriosis will compete with the aromatase expression inhibitor-chicken ovalbumin upstream promoter-transcription factor (COUP-TF) for the same binding site, thereby stimulating the activity of aromatase P450 ( 102 ). Moreover, glucocorticoids and IL1βcan affect the secretion of estrogen by regulating the expression of aromatase promoter 1.4, thereby affecting the occurrence of uterine fibroids ( 103 ).…”
Section: Changes In Aromatase Activity Of Gcs Induce Diseasesmentioning
confidence: 99%
“…When androgen secretion is excessive, the high sensitivity of GCs to FSH causes a large increase in AMH, and AMH in turn inhibits the effect of FSH on aromatase in follicles ( 106 ). Recently, Che et al ( 107 ) found that the highly expressed lncRNA HUPCOS of granulosa cells in patients with PCOS can interact with RNA-binding protein with multiple splicing (RBPMS) and inhibit the expression of aromatase, thereby mediating the excess of androgen in the follicular fluid of PCOS patients Therefore, the decrease in the aromatase activity conversely helps maintain high androgen levels ( 102 , 107 ). In addition, CYP19A1 and A-Kinase anchor protein 95 (AKAP95) levels are significantly decreased in human luteinized GCs of patients with PCOS.…”
Section: Changes In Aromatase Activity Of Gcs Induce Diseasesmentioning
confidence: 99%